Research paper competition - Jolius, Gimbun (Penerbit UMP, 2013)
30th March 2013, Petaling Jaya- Ms Lee Hua Chyn, a master student joint-supervised by Drs. Cheng Chin Kui and Jolius Gimbun from the Faculty of Chemical and Natural Resources Engineering (FKKSA) has won herself a travel grant totaling RM3000 to attend the prestigious 9th World Congress of Chemical Engineering to be held from 18th to 23rd August 2013 at Seoul, Korea. Lee was adjudged the winner for Research Paper Competition organized by Chemical Engineering Technical Division (CETD), The Institution of Engineers Malaysia (IEM).